Kebijakan Program Kota Tanpa Kumuh (KOTAKU) Dalam Mewujudkan Permukiman yang Layak Huni, Produktif, dan Berkelanjutan di Desa Tembuku - Ni Putu Mitasari; I Dewa Ayu Putri Wirantari; I Ketut Winaya (CV. Lenggogeni Data Publishing, 2023)
Problems related to housing and slum settlements occur because of population growth, population dynamics, and the increasing socio-economic demands of the community. The government's efforts to prevent slum settlements by accelerating infrastructure improvements and handling slums in every region in Indonesia by establishing the City Without Slums (KOTAKU) program which is a strategy from the Directorate General of Human Settlement as an element of the implementation of the Ministry of Public Works and Public Housing. This study aims to find out how the No Slum Program Policy (KOTAKU) is in Creating Livable, Productive and Sustainable Settlements in Tembuku Village. This study uses a qualitative descriptive research type by examining primary and secondary data sources. The informant determination technique in this study used purposive sampling. This study uses the theory of public policy processes. The results of the study show that the KOTAKU program's policies in realizing livable, productive and sustainable settlements in Tembuku Village are quite good, which is based on indicators of policy success (Riant Nugroho) which can be measured by the